ԲԱԲԱՋԱՆՅԱՆԱԿԱՆ ԱՎԱՆԴՈՒՅԹՆԵՐԻ ԺԱՌԱՆԳՈՐԴԸ - Գեվորգի Արմենյան, Նարինե; Ռուբենի Ալթույան, Ալիսա (Musical Armenia, 2011)
The portrait-article of the pianist, pedagogue of Yerevan State Conservatory after Komitas Narine G. Armenakyan and pianist, Docent of Yerevan State Conservatory after Komitas Alisa R. Altunyan "Inheritress of Babajanyan traditions" is dedicated to honorable artist RA, Yerevan State Conservatory after Komitas Professor Rosa Tandilyan's 50th anniversary of pedagogical activities. The authors also write statements of famous Russian and Armenian musicians of the wonderful pianist. The characteristics of R.A.Tandilyan is also given, showing him as a wonderful concertmaster and propagandist of the works of Armenian composers.